A Breakthrough In Preventing Circulation of Counterfeit Goods: Adopting Technoreligy in e-Commerce - Purwanto, Purwanto (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
This study aims to examine the role of religion and technoreligy in campaigning the prevention of the sale of counterfeit goods via online. Technoreligy design paradigm in marketing empirically contribute to the restoration of the environment of e-commerce in preventing the circulation of counterfeit goods. Web design combined with religious propaganda and ethics that representing the concept of global e-commerce design is increasingly widespread. By using attention restoration theory, this research connects technoreligy design with the crime of buying counterfeit goods; that is, making consumers aware of avoiding buying counterfeit goods. A series of experiments show the consistency of technoreligy design by exploring consumer responses to religious elements depending on the purpose of their shopping trip (browsing vs. deliberate order) and whether they pay full price or discount. Keywords: Technoreligy, Attention restoration theory, counterfeit, environmental e-Commerce.